Tax Incentives for Research and Development - Correa, Paulo G.; Guceri, Irem (World Bank, Washington, DC, 2016)
This paper aims to discuss the use of tax incentives for the promotion of business expenditures on Research and Development (RD). In the 1980s, only a few countries, including Canada, the United States and France, were implementing tax breaks for RD. By the 2000s, however, many countries from both the developed and the developing world had adopted policy packages that included a version of tax breaks for RD activity. In view of this trend, the question of the effectiveness of RD tax incentive schemes in generating additional privately funded RD has become ever more important.